The Role of Venous Blood Gas Analysis in Medicolegal Evaluation of the Poisoning Cases: A Case Report - Gürbeden, Burçin; Karaman, Gökçe; Özkan, Devrim Sertaç; Uyanıker, Zehra Demiroğlu; Özdemir, Mehmet Hakan (The Bulletin of Legal Medicine, 2017)
Poison is a substance that may cause permanent damage or death by adverse effects on biological systems when certain amount of this substance is taken.  In medicolegal assessment of poisoning cases, the criteria defined in the part “Assessment of injury severity in poisoning cases” in the guide of “Assessment of mutilation crimes defined in Turkish Criminal Code in terms of forensic medicine” is used. But blood gas measurements don’t exist in these criteria. On the other hand, it is not stated that the measurements in the guide are venous or arterial.Our case is 26 years old male. He applied to our department in December 2014 after request of legal authorities. According to medical records and history taken by us, he didn’t get any illness and it was seen that in November 2014, after using different type of alcohol, he consulted to the public health center with the complaints of nausea, vomiting, dizziness and numbness in hands and feet. It was understood that he was oriented, cooperative, conscious and his general condition was good, and he was sent to the Dokuz Eylül University Hospital Emergency Service for medical follow-up. System examinations were normal and he was diagnosed as ethyl alcohol intoxication. In medical records; laboratory results of blood alcohol (ethanol) level and venous blood gas measurements were seen. It was observed that there was no problem in medical follow-up of patient and he was discharged at the same day.The difficulties were experienced in medicolegal assessment of this case because of that the blood gas measurements for determining life-threatening injuries were not stated as venous or arterial in the guide used for determining severity of injury. It will be discussed that is existing of venous blood gas measurements in the guide going to be helpful or not.
Keywords: intoxication; venous blood gas; medicolegal assessment